PELATIHAN PEMELIHARAN LEBAH TRIGONA SPP DI DUSUN TUAKONA DESA KECAMATAN JAILOLO SELATAN KABUPATEN HALMAHERA BARAT - Nur Sjafani; Suryati Tjokrodiningrat; Yusri Sapsuha; M Ade Salim (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Trigona Spp beekeeping in North Maluku has not been widely practiced, because some people do not know this type of bee. The community also does not know that in addition to producing honey, Trigona Spp. bees also produce propolis which is beneficial for health and has a fairly high economic value. The purpose of Community Service (PKM) is to introduce partners to how to maintain and care for Trigona spp. bees and introduce plant species as a source of food for Trigona spp. bees which are useful for producing honey and propolis. The solution offered by several methods is to approach to find out the problems and conduct counseling and training to solve the problems. Thus, it is expected that partners can understand the importance of good care for Trigona spp. bees, as well as how to choose and plant the right plants as a food source. In addition, through this training, partners are expected to increase the productivity of honey and propolis, so that it can provide better economic benefits for them. The results of the service activities are that the community as partners know how to keep Trigona Spp. bees. The evaluation results show that the community can propagate colonies (grafting) and carry out maintenance of beekeeping stups